Slovak and German connections in the hydronyms of Western Slovakia - Beláková, Mária (Geographical names in physical space, 2016)
Our study deals with the hydronyms in the western region of Slovakia. These proper names petrify some very interesting elements of German lexicon, specifically the language of Bavarian settlers in the 12th to the 15th centuries. We studied this specific feature in the area of Malé Karpaty, near the big watercourses Myjava, Stoličný potok, Blatina, Gidra etc. The most amazing names are those which contain the roots -štún (-štán), -pach (-poch), -perg (-perek, -perk). Some of hydronyms remain unchanged, like Bei den Sicken Linde (the name has only its German form), the others were translated or deformed, for example Holombecká dolina (from Hohlen Weg) or Sebrecký potok (from Sehr Berg).Štúdia je súčasťou riešenia projektu Synchrónna a diachrónna hydronymia Žitného ostrova VEGA 1/0510/12 (2012–2014).